Effect of fungicides on zearalenone synthesis by Fusarium moniliforme - S. SINGH, RAJNI GUPTA and (Indian Phytopathology, 2002)
Zearalenone producing highly toxic strain of Fusarium moniliforme (S2. PR. 49) isolated from the sorghum grains was grown on sterilized moist rice medium, sorghum grains and unsterilized sorghum grains separately, supplemented with 0.1 to 0.5 per cent concentration of thiram, bavistin and dithane. This study revealed that bavistin was the most effective fungicide in inhibiting the zearalenone production at 0.1 percent concentration on the sterilied moist rice medium as well as on the sorghum grains. In the case of unsterilized sorghum grains, bavistin was effective at 0.4 per cent and 0.5 per cent concentration. Bavistin completely inhibited the zearlenone synthesis at 0.2 per cent concentration on both sterilized medium, while dithane and thiram completely inhibited the zearalenone synthesis at 0.3 per cent and 0.4 per cent concentration. Further, on the unsterilized sorghum grains, bavistin completely prevented the zearalenone synthesis at 0.5 per cent concentration while dithane and thiram could not prevent completely zearalenone elaboration at 0.5 per cent concentration.